Spatial trends in a biomagnifying contaminant: Application of amino acid compound–specific stable nitrogen isotope analysis to the interpretation of bird mercury levels. (14th April 2018) - Dolgova, Svetlana; Popp, Brian N.; Courtoreille, Kevin; Espie, Richard H.M.; Maclean, Bruce; McMaster, Mark; Straka, Jason R.; Tetreault, Gerald R.; Wilkie, Steve; Hebert, Craig E.
Abstract: Levels of biomagnifying contaminants are greatest in high–trophic level biota (e.g., predatory birds such as gulls). Gull eggs have been used to assess contaminant spatial patterns and sources, but such assessments must consider how organism trophic position may influence spatial inferences. Stable nitrogen isotopes (δ 15 N) in bulk tissue are routinely used in this context. However, bulk δ 15 N values are only useful if spatial differences in baseline δ 15 N values are considered. Amino acid compound–specific stable nitrogen isotope analysis can generate estimates of baseline δ 15 N values and trophic position from the same sample. In the present study, eggs ( n = 428) of California ( Larus californicus ), herring ( Larus argentatus smithsonianus ), and ring‐billed ( Larus delawarensis ) gulls were used to assess spatial patterns in mercury (Hg) availability in 12 western Canadian lakes located over 14 degrees of latitude, with amino acid compound–specific stable isotope analysis adjustment of egg Hg levels for trophic position. Mean trophic position–adjusted egg Hg levels (micrograms per gram, dry wt) were greatest at sites in receiving waters of the Athabasca River ( X ¯ = 0.70) compared to southern ( X ¯ = 0.39) and northern ( X ¯ = 0.50) regions. Research is required to investigate factors (e.g., local Hg released as a result of human activities, processes influencing Hg methylation) which may be responsible for greater Hg availability in the lower Athabasca River basin. However, it is clear that amino acid compound–specific stable isotope analysis is a valuable tool for assessing contaminant spatial patterns. Environ Toxicol Chem 2018;37:1466–1475. © 2018 SETAC Abstract :